(untitled) (Biological Sciences - PJSIR, 2003)
Dielectric properties of evaporated silicon mono oxide film sandwiched between aluminium electrodes have been studied in the frequency range from 0 . 1 Hz to !MHz . The struct ures were prepa red on glass slide by in situ deposition of aluminium through successive evaporation in vacuum of the order of 10-5 torr. The structures were annealed at tempera tures of 303 °K to 378 °K for five minutes and the effect of annealing is discussed. Dielectric paramters were measured by alternating current (AC) impedence technique of Frequency Response Analvzer. The capacitance C ’ (permitivity), conductance G and the loss factor g" were found to depend on freq uency and temperature, within high frequency range the capacitance varies very slowly, shOthe dielect ric dispersive nature and temperature independ ent at high fre q uencies . The experimental evidence on the freq uency domain behaviour of this structure h ave been discussed . The result s were best analyzed by comparing them ,vith the power law frequency dependence curve which departs from Debye like dielecric behaviour. The a.c cond uctance G of such samples varies dircctity to (co") , ol being the circular frequency, and n is a number, which is less than one and is a temperature dependent quantity. The slope of loss curve is not symme-trical with the loss peak. It is emphasised that these experimental results cannot be analysed in terms of quantum hopping cond uction mechanism proposed by Johnschere . The aim of this investigation is to study the dielec tric response in the specific temperature range of deposited SiO films and to prepare initially the low cost Schottky diodes and other basic components